Etude expérimentale et théorique d’un nouveau composé halogène pnicture Hg$_{12}$Sb$_6 ($Br$_{5,186}$I$_{6,814})$ - Kheit, Messaoud; Merazka, Soumia; Kars, Mohammed; Gómez-Herrero, Adrian; Roisnel, Thierry; Sidoumou, Mohamed (Comptes Rendus. Chimie)
We synthesized the compound $Hg_{12}Sb_6(Br_{5,186}I_{6,814})$ by chemical vapour transport method. Its structure was determined by single crystal X-ray diffraction. The optical band gap was determined as 2,1 eV according to UV${-}$vis diffuse reflectance spectroscopy. Furthermore, the photocatalytic experiments have shown the ability of the $Hg_{12}Sb_6$ ($Br_{5,186}I_{6,814}$) to degrade rhodamine B (RhB) under solar light radiation. The ab initio calculations using the CASTEP code give a gap of 1,7 eV in good agreement with that found experimentally.